Laparoscopic hemostasis and drainage for postpartum retroperitoneal hematoma complicated with an infection: A case report and surgical video. (May 2022) - Yokoe, Takuya; Kita, Masato; Suzuki, Kentaro; Butsuhara, Yusuke; Yoshida, Aya; Morikawa, Mamoru; Okada, Hidetaka
Abstract: Introduction: and importance: Postpartum retroperitoneal hematomas are a potential complication of childbirth. The management of secondary infections of such hematomas has not been fully elucidated. We present a typical case of such management via laparoscopic surgery, and include a surgical video. Case presentation: A woman in her 20s experienced fever and right lower quadrant pain and distension on postpartum day 2. Pelvic examination revealed a hump on the vaginal wall on the right side of the uterine cervix, and ultrasonography revealed a hematoma. Contrast-enhanced computed tomography revealed no active extravasation into the hematoma. Conservative antibiotic treatment was started; however, on postpartum day 6, her pain increased and her C-reactive protein concentration and white blood cell count were high. Magnetic resonance imaging revealed a paravaginal/upper vaginal wall hematoma (80 × 70 × 63 mm) located to the right of the uterus and bladder. Hence, laparoscopic drainage was performed on postpartum day 7. The retroperitoneal hematoma was incised and drained. The source of bleeding was the right vaginal vein, and bleeding was halted via electrocoagulation. The patient's symptoms improved immediately, and the postoperative course was uneventful. Clinical discussion: The laparoscopic approach enabled immediate hemostasis and identification of the source of bleeding. The drainage route was cleaner than would be possible via a vaginal approach, possibly preventing postoperative retrograde re-infection. Conclusion: Laparoscopic surgery for postpartum retroperitoneal hematoma with infection was useful for both drainage and hemostasis. Highlights: Laparoscopic treatment of a retroperitoneal postpartum hematoma with infection. Laparoscopy enabled sufficient drainage and surgical hemostasis of this hematoma. Laparoscopic drainage prevented retrograde re-infection via vaginal drainage.